The Effect Of Integrated Neuromuscular Inhibition Technique On Improving Neck Functional Ability In Tension-Type Headache - Virny Dwiya Lestari; Rahmat Nugraha Akib; Aco Tang (UNIVERSITAS NEGERI MAKASSAR, 2023)
Tension-type headache is one of the most common complaints of musculoskeletal pain due to myofascial trigger points. The presence of pain and soreness in the neck and head, tightness, stiffness, spasms, and limitation of motion is a complaint that is often experienced by patients. Methods: This study aims to determine the effect of the Integrated Neuromuscular Inhibition Technique exercise on increasing the functional ability of the neck in Tension-Type Headache conditions. This research is a pre-experimental study with a pre-test and post-test one-group design using an accidental sampling technique with a total sample of 30 people. The place of research was conducted at the Telkomedika Makassar Clinic. A tool to measure the functional ability of the neck using the Neck Disability Index (NDI). Result: The results of the study were an increase in the functional ability of the neck based on measurements of the Neck Disability Index (NDI), namely a pre-test value of 48.80 to a post-test of 41.13 in the condition of Tension-Type Headache at the Telkomedika Clinic Makassar because after being given Integrated Neuromuscular Inhibition Technique therapy (INIT) decreased neck pain, decreased spasm of the neck muscles, and increased functional ability of the neck. Conclusion: Integrated Neuromuscular Inhibition Technique exercises can improve the functional ability of the neck in Tension-Type Headache conditions at the Telkomedika Clinic in Makassar.